2023
DOI: 10.1002/adfm.202307896
|View full text |Cite
|
Sign up to set email alerts
|

Lead‐Free Halide Perovskite Materials and Optoelectronic Devices: Progress and Prospective

Iago López‐Fernández,
Donato Valli,
Chun‐Yun Wang
et al.

Abstract: Halide perovskites, in the form of thin films and colloidal nanocrystals, have recently taken semiconductor optoelectronics research by storm, and have emerged as promising candidates for high‐performance solar cells, light‐emitting diodes (LEDs), lasers, photodetectors, and radiation detectors. The impressive optical and optoelectronic properties, along with the rapid increase in efficiencies of solar cells and LEDs, have greatly attracted researchers across many disciplines. However, most advances made so fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 514 publications
0
15
0
Order By: Relevance
“…Lead-free halide perovskites can be achieved by homovalent (Sn 2+ and Ge 2+ ) or heterovalent (Bi 3+ , Sb 3+ , Cu + , In 3+ ) substitution of Pb 2+ ions. The heterovalent substitution of Pb 2+ leads to a substantially high bandgap, therefore, their optoelectronic characteristics are limited to defect states, leading to a lower absorption coefficient . In the homovalent substitution, Sn 2+ is considered an obvious choice for replacement of Pb 2+ owing to its low toxicity, similar ionic radius, and lower band gap than lead-based perovskites, etc. , Hong et al have shown that an emissive layer of CsSnI 3 , processed at room temperature, used in an IR-LED exhibits an external quantum efficiency (EQE) of 3.8% and a maximum radiance of 40 W.sr –1 .m –2 .…”
Section: Introductionmentioning
confidence: 99%
“…Lead-free halide perovskites can be achieved by homovalent (Sn 2+ and Ge 2+ ) or heterovalent (Bi 3+ , Sb 3+ , Cu + , In 3+ ) substitution of Pb 2+ ions. The heterovalent substitution of Pb 2+ leads to a substantially high bandgap, therefore, their optoelectronic characteristics are limited to defect states, leading to a lower absorption coefficient . In the homovalent substitution, Sn 2+ is considered an obvious choice for replacement of Pb 2+ owing to its low toxicity, similar ionic radius, and lower band gap than lead-based perovskites, etc. , Hong et al have shown that an emissive layer of CsSnI 3 , processed at room temperature, used in an IR-LED exhibits an external quantum efficiency (EQE) of 3.8% and a maximum radiance of 40 W.sr –1 .m –2 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high toxicity, instability in the presence of heat, oxygen, moisture, and light, the exceptional optoelectronic properties of lead-based metal halide perovskites find great acceptance in real-world applications and make it the much desired material class in the field of photovoltaic applications. Owing to the efforts of researchers worldwide, these halide perovskites have found extended applicability in sustainable energy-harvesting and storage devices, , LEDs, photodetectors, piezoelectric nanogenerators, and so on. However, the toxicity of lead-based compositions cannot be overlooked, and scientists are constantly making efforts to find a better alternative compound. In this regard, the all–inorganic, lead-free halide double-perovskites are making a niche for themselves. For example, the Cs 2 AgBiCl 6 (CABC) and Cs 2 AgInCl 6 (CAIC) compositions show excellent thermal and air stabilities but pose a challenge in its direct induction into the optoelectronic application industry. Cs 2 AgBiCl 6 is reported to have an indirect band gap of ∼2.5 eV, resulting in a weak optical absorption and emission response.…”
Section: Introductionmentioning
confidence: 99%
“…Lead halide-based perovskites show excellent properties relevant for solar cells, LEDs, photodetectors, chiral optoelectronics, and quantum light emitters. These findings prompted researchers to explore environmentally benign Pb-free halide perovskites. Consequently, halide-based double perovskites with the generic formula Cs 2 BB′X 6 (B = Ag, Na; B′ = Bi, In, Sb; X = Cl, Br) emerged as a versatile class of material, that retain the three-dimensional (3D) perovskite crystal structure, as shown in Figure a. But the halide double perovskites have either a wide band gap and/or a forbidden optical transition across the band gap, limiting their optical and optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%